Method for increasing iron-phosphorus ratio of iron phosphate material
By using raw materials and catalysts such as ammonium phosphate, ferrous titanium dioxide and ferrous sulfate in the preparation process, the reaction conditions are controlled, and the problem of improving the iron-iron-phosphate ratio and crystallinity in the prior art is solved, and efficient and low-cost preparation of iron-iron-phosphate is achieved. The product has high-iron-phosphate ratio and good crystallinity.
Patent Information
- Application Number
- CN202411749767.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art has problems of high costs, low production efficiency and poor stability in improving the iron-phosphorus ratio and crystallinity of iron phosphate. Especially in high temperature and high pressure environments, equipment costs and energy consumption increase, and production safety and efficiency decrease.
By using ammonium phosphate and phosphoric acid as the phosphorus source, ferrous titanium dioxide as the iron source, hydrogen peroxide as the oxidizing agent, and ferrous sulfate as the catalyst, the reaction conditions and process steps, including the synthesis, conversion and calcining steps, are controlled to improve the iron-phosphorus ratio and crystallinity of iron phosphate.
The high-iron-phosphorus ratio is achieved under low phosphoric acid dosage, and the Fe/P of the finished iron phosphate reaches more than 98%, the grains are developed intact, the crystallinity is high, and the grains are extremely resistant to high temperatures and have stable structure, which reduces process costs and environmental pressure.
Smart Images

Figure CN119706767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a method for improving the iron-phosphorus ratio of an iron phosphate material. Background Art
[0002] Iron phosphate, also known as ferrous phosphate and orthophosphate, is an inorganic compound. The properties of iron phosphate, such as iron-phosphorus ratio and morphology, can significantly affect its electrical properties and compaction at the iron-lithium end. Simply put, the larger the iron phosphate grains, the better the crystal development and the higher the iron-phosphorus ratio, the better the electrical properties after calcination into iron-lithium, but the compaction strength will be low. Therefore, the lithium iron phosphate obtained from iron phosphates of different properties has different indicators, and its application scenarios are also different. In the field of energy storage, there are certain requirements for the cycle performance and rate capacity performance of the battery, while the requirements for compaction density are relaxed, and the corresponding iron phosphate material needs to have a higher iron-phosphorus ratio and crystallinity. Under conventional processes, in order to obtain this type of iron phosphate, a large amount of phosphoric acid is usually required, and the pressure on wastewater treatment is increased, which significantly increases the process and environmental costs. How to increase the crystallinity of iron phosphate at a lower process cost, people have tried many methods, such as using high-temperature and high-pressure reactors, extending the reaction time, and recycling mother liquor phosphoric acid, but these methods have the following problems: 1. High temperature and high pressure reactor: High temperature and high pressure environment can increase the reversibility of the reaction, thereby obtaining well-developed iron phosphate grains and increasing the iron-phosphorus ratio of iron phosphate. However, the high temperature and high pressure synthesis environment poses a challenge to production safety, increases production energy consumption and reduces production efficiency. The purchase and maintenance costs of the equipment are also higher than those of conventional reactors.
[0003] 2. Prolong the reaction time: production efficiency is reduced, process energy consumption is increased, and the effect of increasing the iron-phosphorus ratio is limited.
[0004] 3. Reuse of mother liquor phosphoric acid: Reuse of mother liquor can significantly reduce production costs, but due to process losses, new phosphoric acid needs to be supplemented each time and the ammonia nitrogen ratio of the mother liquor will fluctuate with each cycle, which is not conducive to production stability. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for improving the iron-phosphorus ratio of iron phosphate materials, using ammonium phosphate and phosphoric acid as phosphorus sources, the phosphorus source concentration is controlled at 0.5-2.0 mol / L, and titanium dioxide ferrous iron after impurity removal is used as the iron source, the iron source concentration is controlled at 0.5-2.0 mol / L, the use ratio of the iron-phosphorus source is controlled between 0.8-1.2, hydrogen peroxide is used as an oxidant, ferrous sulfate is used as a catalyst, the overall process route is divided into a synthesis stage and a conversion stage with temperature increase conversion as a node, and a washing step is added between the two stages to reduce the impurity content in the finished product.
[0006] The specific steps include: S1. Raw material preparation: prepare 0.5-2.0 mol / L ammonium phosphate solution, 0.5-2.0 mol / L phosphoric acid solution, 0.5-2.0 mol / L titanium dioxide ferrous solution, and 30% hydrogen peroxide; S2, synthesis: the ammonium phosphate solution, titanium dioxide ferrous solution and hydrogen peroxide prepared in step S1 are added into a reaction container, and the mixture is kept warm for 30-60 min to obtain a slurry, and the slurry is filtered and washed until the conductivity of the washing water is less than 4000 μS / cm to obtain a yellow washed filter cake; S3, conversion: weigh 5-15 kg of pure water, add 200-400 g of ferrous sulfate and 200-600 g of the phosphoric acid solution prepared in step S1 to dissolve them, add 2.5-3.5 kg of the yellow first-wash filter cake obtained in step S2, after 15-25 min of slurrying, heat to 90-94 ° C, keep warm for 1 hour, filter and wash with suction to obtain a pink second-wash filter cake; S4, calcination: drying the pink second-wash filter cake to obtain ferric phosphate dihydrate, calcining and crushing the ferric phosphate dihydrate to obtain finished ferric phosphate.
[0007] Moreover, in step S1, the pH of the ammonium phosphate solution is 6.5-7.5.
[0008] Moreover, in step S2, according to the ratio of the amount of substances, titanium dioxide ferrous solution: ammonium phosphate solution = 0.8-1.2.
[0009] Moreover, in step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: pure water is used as the base, the ammonium phosphate solution and the titanium dioxide ferrous solution are added into the reaction container in parallel, and then the hydrogen peroxide is added.
[0010] Moreover, in the step S2, the feeding rate of the titanium dioxide ferrous solution and the phosphorus source is 100-300 ml / min.
[0011] Moreover, in the step S2, the feeding rate of hydrogen peroxide is 5-15 ml / min, and the reaction temperature is 30-60°C.
[0012] Moreover, in step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: using the titanium dioxide ferrous solution as the base, mixing the ammonium phosphate solution and the hydrogen peroxide solution and then adding them into the reaction container in a single stream.
[0013] Furthermore, in the step S2, the ammonium phosphate solution and the hydrogen peroxide are mixed and added in a single stream at a feeding rate of 100-300 ml / min, and the reaction temperature is 30-60°C.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention introduces ferrous sulfate as a catalyst in the process of generating ammonium ferric phosphate by reacting ammonium phosphate, ferrous titanium dioxide and hydrogen peroxide, and converting the ammonium ferric phosphate into ferric phosphate crystals, thereby obtaining a high iron-phosphorus ratio material at a low phosphoric acid dosage. The Fe / P ratio of the finished ferric phosphate prepared by the present invention is above 98%, the acid iron grains are well developed and the crystallinity is high. At the same time, the specific surface area of the finished ferric phosphate prepared by the present invention is maintained at 13.3 m2 / g and 15.2 m2 / g, and the ferric phosphate grains are extremely resistant to high temperatures and have a stable structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 From top to bottom are respectively the SEM image of ferric phosphate dihydrate obtained in Example 3, the SEM image of the finished ferric phosphate, and the XRD image of ferric phosphate dihydrate; Figure 2 From top to bottom, they are respectively the SEM image of ferric phosphate dihydrate obtained in Example 6, the SEM image of the finished ferric phosphate, and the XRD image of ferric phosphate dihydrate; Figure 3 From top to bottom, they are respectively the SEM image of the iron phosphate dihydrate obtained in Comparative Example 1, the SEM image of the finished iron phosphate, and the XRD image of the iron phosphate dihydrate; Figure 4 From top to bottom are the SEM image of ferric phosphate dihydrate obtained in comparative example 2, the SEM image of the finished ferric phosphate, and the XRD image of ferric phosphate dihydrate. DETAILED DESCRIPTION
[0016] Example 1 A method for improving the iron-phosphorus ratio of an iron phosphate material comprises the following steps: S1. Raw material preparation: prepare 0.5 mol / L ammonium phosphate solution, 0.5 mol / L phosphoric acid solution, 0.5 mol / L titanium dioxide ferrous solution, and 30% hydrogen peroxide; S2, synthesis: the ammonium phosphate solution, titanium dioxide ferrous solution and hydrogen peroxide prepared in step S1 are added into a reaction container, and the mixture is kept warm for 30 min to obtain a slurry, and the slurry is filtered and washed until the conductivity of the washing water is less than 4000 μS / cm to obtain a yellow washed filter cake; S3, conversion: weigh 5 kg of pure water, add 200 g of ferrous sulfate and 200 g of the phosphoric acid solution prepared in step S1 to dissolve them, add 2.5 kg of the yellow first-wash filter cake obtained in step S2, after 15 minutes of complete slurrying, heat to 90 ° C, keep warm for 1 hour, filter and wash with suction to obtain a pink second-wash filter cake; S4, calcination: drying the pink second-wash filter cake to obtain ferric phosphate dihydrate, calcining and crushing the ferric phosphate dihydrate to obtain finished ferric phosphate.
[0017] Moreover, in step S1, the pH of the ammonium phosphate solution is 6.5.
[0018] Moreover, in the step S2, the ratio of the amount of substances is titanium dioxide ferrous solution: ammonium phosphate solution = 0.8.
[0019] Moreover, in the step S2, the ratio of the amounts of substances is ferrous titanium dioxide solution: ammonium phosphate solution: hydrogen peroxide solution = 1:1.00:0.60.
[0020] Moreover, in step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: pure water is used as the base, the ammonium phosphate solution and the titanium dioxide ferrous solution are added into the reaction container in parallel, and then the hydrogen peroxide is added.
[0021] Moreover, in step S2, the feeding rate of the titanium dioxide ferrous solution and the phosphorus source is 100 ml / min.
[0022] Moreover, in the step S2, the feeding rate of hydrogen peroxide is 5 ml / min, and the reaction temperature is 30°C.
[0023] Example 2 A method for improving the iron-phosphorus ratio of an iron phosphate material comprises the following steps: S1. Raw material preparation: prepare 2.0 mol / L ammonium phosphate solution, 2.0 mol / L phosphoric acid solution, 2.0 mol / L titanium dioxide ferrous solution, and 30% hydrogen peroxide; S2, synthesis: the ammonium phosphate solution, titanium dioxide ferrous solution and hydrogen peroxide prepared in step S1 are added into a reaction container, and the mixture is kept warm for 60 min to obtain a slurry, and the slurry is filtered and washed until the conductivity of the washing water is less than 4000 μS / cm to obtain a yellow washed filter cake; S3, conversion: weigh 15 kg of pure water, add 400 g of ferrous sulfate and 600 g of the phosphoric acid solution prepared in step S1 to dissolve them, add 3.5 kg of the yellow first-wash filter cake obtained in step S2, after 25 minutes of slurrying, heat to 94 ° C, keep warm for 1 hour, filter and wash with suction to obtain a pink second-wash filter cake; S4, calcination: drying the pink second-wash filter cake to obtain ferric phosphate dihydrate, calcining and crushing the ferric phosphate dihydrate to obtain finished ferric phosphate.
[0024] Moreover, in step S1, the pH of the ammonium phosphate solution is 7.5.
[0025] Moreover, in the step S2, according to the ratio of the amount of substances, the titanium dioxide ferrous solution: ammonium phosphate solution = 1.2. Moreover, in the step S2, according to the ratio of the amount of substances, the titanium dioxide ferrous solution: ammonium phosphate solution: hydrogen peroxide = 1: 1.08: 0.65.
[0026] Moreover, in step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: pure water is used as the base, the ammonium phosphate solution and the titanium dioxide ferrous solution are added into the reaction container in parallel, and then the hydrogen peroxide is added.
[0027] Moreover, in step S2, the feeding rate of the titanium dioxide ferrous solution and the phosphorus source is 300 ml / min.
[0028] Moreover, in step S2, the feeding rate of hydrogen peroxide is 15 ml / min, and the reaction temperature is 60°C.
[0029] Example 3 A method for improving the iron-phosphorus ratio of an iron phosphate material comprises the following steps: S1. Raw material preparation: prepare 1 mol / L ammonium phosphate solution, 1 mol / L phosphoric acid solution, 1 mol / L titanium dioxide ferrous solution, and 30% hydrogen peroxide; S2, synthesis: the ammonium phosphate solution, titanium dioxide ferrous solution and hydrogen peroxide prepared in step S1 are added into a reaction container, and the mixture is kept warm for 45 minutes to obtain a slurry, and the slurry is filtered and washed until the conductivity of the washing water is less than 4000 μS / cm to obtain a yellow washed filter cake; S3, conversion: weigh 10 kg of pure water, add 300 g of ferrous sulfate and 400 g of the phosphoric acid solution prepared in step S1 to dissolve them, add 3 kg of the yellow first-wash filter cake obtained in step S2, after 20 minutes of slurrying, heat to 92 ° C, keep warm for 1 hour, filter and wash with suction to obtain a pink second-wash filter cake; S4, calcination: drying the pink second-wash filter cake to obtain ferric phosphate dihydrate, calcining and crushing the ferric phosphate dihydrate to obtain finished ferric phosphate.
[0030] Moreover, in step S1, the pH of the ammonium phosphate solution is 7.
[0031] Moreover, in the step S2, according to the ratio of the amount of substances, titanium dioxide ferrous solution: ammonium phosphate solution = 1.
[0032] Moreover, in the step S2, the ratio of the amounts of substances is: titanium dioxide ferrous solution: ammonium phosphate solution: hydrogen peroxide = 1:1.04:0.63.
[0033] Moreover, in step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: pure water is used as the base, the ammonium phosphate solution and the titanium dioxide ferrous solution are added into the reaction container in parallel, and then the hydrogen peroxide is added.
[0034] Moreover, in step S2, the feeding rate of the titanium dioxide ferrous solution and the phosphorus source is 200 ml / min.
[0035] Moreover, in step S2, the feeding rate of hydrogen peroxide is 10 ml / min, and the reaction temperature is 45°C.
[0036] Example 4 A method for improving the iron-phosphorus ratio of an iron phosphate material comprises the following steps: S1. Raw material preparation: prepare 0.5 mol / L ammonium phosphate solution, 0.5 mol / L phosphoric acid solution, 0.5 mol / L titanium dioxide ferrous solution, and 30% hydrogen peroxide; S2, synthesis: the titanium dioxide ferrous solution prepared in step S1 is put into a reaction container, the ammonium phosphate solution and the hydrogen peroxide solution are mixed, and then put into the reaction container, and after keeping warm for 30 minutes, a slurry is obtained, and the slurry is filtered and washed until the conductivity of the washing water is less than 4000 μS / cm to obtain a yellow washed filter cake; S3, conversion: weigh 5 kg of pure water, add 200 g of ferrous sulfate and 200 g of the phosphoric acid solution prepared in step S1 to dissolve them, add 2.5 kg of the yellow first-wash filter cake obtained in step S2, after 15 minutes of complete slurrying, heat to 90 ° C, keep warm for 1 hour, filter and wash with suction to obtain a pink second-wash filter cake; S4, calcination: drying the pink second-wash filter cake to obtain ferric phosphate dihydrate, calcining and crushing the ferric phosphate dihydrate to obtain finished ferric phosphate.
[0037] Moreover, in step S1, the pH of the ammonium phosphate solution is 6.5.
[0038] Moreover, in the step S2, the ratio of the amounts of substances is: titanium dioxide ferrous solution: ammonium phosphate solution: hydrogen peroxide = 1:1.02:0.65.
[0039] Moreover, in step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: the titanium dioxide ferrous solution is used as the base, and the ammonium phosphate solution and the hydrogen peroxide solution are mixed evenly and then added into the reaction container in a single stream.
[0040] Moreover, in the step S2, the rate of single-stream feeding of the titanium dioxide ferrous solution and the hydrogen peroxide solution after mixing is 100 ml / min.
[0041] Furthermore, in the step S2, the reaction temperature is 30°C.
[0042] Example 5 A method for improving the iron-phosphorus ratio of an iron phosphate material comprises the following steps: S1. Raw material preparation: prepare 2.0 mol / L ammonium phosphate solution, 2.0 mol / L phosphoric acid solution, 2.0 mol / L titanium dioxide ferrous solution, and 30% hydrogen peroxide; S2, synthesis: the titanium dioxide ferrous solution prepared in step S1 is put into a reaction container, the ammonium phosphate solution and the hydrogen peroxide solution are mixed, and then put into the reaction container, and after keeping warm for 60 minutes, a slurry is obtained, and the slurry is filtered and washed until the conductivity of the washing water is less than 4000 μS / cm to obtain a yellow washed filter cake; S3, conversion: weigh 15 kg of pure water, add 400 g of ferrous sulfate and 600 g of the phosphoric acid solution prepared in step S1 to dissolve them, add 3.5 kg of the yellow first-wash filter cake obtained in step S2, after 25 minutes of slurrying, heat to 94 ° C, keep warm for 1 hour, filter and wash with suction to obtain a pink second-wash filter cake; S4, calcination: drying the pink second-wash filter cake to obtain ferric phosphate dihydrate, calcining and crushing the ferric phosphate dihydrate to obtain finished ferric phosphate.
[0043] Moreover, in step S1, the pH of the ammonium phosphate solution is 7.0.
[0044] Moreover, in the step S2, the ratio of the amounts of substances is: titanium dioxide ferrous solution: ammonium phosphate solution: hydrogen peroxide = 1:1.02:0.65.
[0045] Moreover, in step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: the titanium dioxide ferrous solution is used as the base, and the ammonium phosphate solution and the hydrogen peroxide solution are mixed evenly and then added into the reaction container in a single stream.
[0046] Moreover, in the step S2, the rate of single-stream feeding of the titanium dioxide ferrous solution and hydrogen peroxide after mixing is 300 ml / min.
[0047] Furthermore, in the step S2, the reaction temperature is 60°C.
[0048] Example 6 A method for improving the iron-phosphorus ratio of an iron phosphate material comprises the following steps: S1. Raw material preparation: prepare 1 mol / L ammonium phosphate solution, 1 mol / L phosphoric acid solution, 1 mol / L titanium dioxide ferrous solution, and 30% hydrogen peroxide; S2, synthesis: the titanium dioxide ferrous solution prepared in step S1 is put into a reaction container, the ammonium phosphate solution and the hydrogen peroxide solution are mixed, and then put into the reaction container, and after keeping warm for 45 minutes, a slurry is obtained, and the slurry is filtered and washed until the conductivity of the washing water is less than 4000 μS / cm to obtain a yellow washed filter cake; S3, conversion: weigh 10 kg of pure water, add 300 g of ferrous sulfate and 400 g of the phosphoric acid solution prepared in step S1 to dissolve them, add 3 kg of the yellow first-wash filter cake obtained in step S2, after 20 minutes of slurrying, heat to 92 ° C, keep warm for 1 hour, filter and wash with suction to obtain a pink second-wash filter cake; S4, calcination: drying the pink second-wash filter cake to obtain ferric phosphate dihydrate, calcining and crushing the ferric phosphate dihydrate to obtain finished ferric phosphate.
[0049] Moreover, in step S1, the pH of the ammonium phosphate solution is 7.5.
[0050] Moreover, in the step S2, the ratio of the amounts of substances is: titanium dioxide ferrous solution: ammonium phosphate solution: hydrogen peroxide = 1:1.02:0.65.
[0051] Moreover, in step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: the titanium dioxide ferrous solution is used as the base, and the ammonium phosphate solution and the hydrogen peroxide solution are mixed evenly and then added into the reaction container in a single stream.
[0052] Moreover, in the step S2, the rate of single-stream feeding of the titanium dioxide ferrous solution and hydrogen peroxide after mixing is 300 ml / min.
[0053] Furthermore, in the step S2, the reaction temperature is 45°C.
[0054] Comparative Example 1 The difference between this comparative example and Example 3 is that in step S3, ferrous sulfate is not added.
[0055] Comparative Example 2 The difference between this comparative example and Example 6 is that in step S3, ferrous sulfate is not added.
[0056] Experimental Section
[0057] Experiment 1 The iron phosphate dihydrate and the finished iron phosphate obtained in Example 3 were scanned by electron microscope, and the iron phosphate dihydrate obtained in Example 3 was analyzed by X-ray. The results are as follows: Figure 1 As shown, Figure 1 From top to bottom in the figure are respectively the SEM image of ferric phosphate dihydrate obtained in Example 3, the SEM image of the finished ferric phosphate, and the XRD image of ferric phosphate dihydrate.
[0058] As can be seen from the figure, after ferrous sulfate is introduced into the conversion mother liquor, the primary particles of the finished iron phosphate are well developed, the size of each particle is greater than 100 nm, the particle thickness is large, and the XRD spectrum of ferrous phosphate dihydrate shows that the phase is monoclinic, and the high diffraction peak intensity indicates good crystallinity of the grains; after high-temperature calcination, the primary particles adhere to each other, and the whole is still loose and porous.
[0059] Experiment 2 The iron phosphate dihydrate and the finished iron phosphate obtained in Example 6 were scanned by electron microscope, and the iron phosphate dihydrate obtained in Example 6 was analyzed by X-ray. The results are as follows: Figure 2 As shown, Figure 2 From top to bottom in the figure are respectively the SEM image of ferric phosphate dihydrate obtained in Example 6, the SEM image of the finished ferric phosphate, and the XRD image of ferric phosphate dihydrate.
[0060] from Figure 2 It can be seen from the morphology of ferrous phosphate dihydrate that after the addition of ferrous sulfate during the conversion process, the primary particles of ferric phosphate are in the form of small flakes of a certain thickness, and the flakes are irregularly stacked; the X-ray diffraction spectrum of ferric phosphate dihydrate shows an obvious peak shape of ferric phosphate dihydrate, and even without high-temperature calcination, the diffraction peak of the crystal is very strong, showing good crystallinity; after high-temperature calcination, the primary particles adhere to each other, and the whole is still loose and porous.
[0061] Experiment 3 The iron phosphate dihydrate obtained in Comparative Example 1 and the finished iron phosphate were subjected to electron microscope scanning, and the iron phosphate dihydrate obtained in Comparative Example 1 was subjected to X-ray analysis. The results are as follows: Figure 3 As shown, Figure 3 From top to bottom in the figure are respectively the SEM image of ferric phosphate dihydrate obtained in comparative example 1, the SEM image of the finished ferric phosphate, and the XRD image of ferric phosphate dihydrate.
[0062] from Figure 3 It can be seen from the SEM morphology of ferric phosphate dihydrate that the primary particles of iron phosphate in comparative example 1 are in the shape of millet grains and are stacked disorderly as a whole. Compared with the morphology of ferric phosphate dihydrate in Example 3, the primary particle size of the conventional process is obviously smaller, the particle development is incomplete, and after calcination under the same conditions, there is severe melting between the grains; the XRD spectrum shows that the phase is still a monoclinic phase, but the overall peak intensity is not high.
[0063] Experiment 4 The iron phosphate dihydrate and the finished iron phosphate obtained in Comparative Example 2 were scanned by electron microscope, and the pink iron phosphate dihydrate of the second-wash filter cake obtained in Comparative Example 2 was analyzed by X-ray. The results are as follows: Figure 4 As shown, Figure 4 From top to bottom in the figure are respectively the SEM image of ferric phosphate dihydrate obtained in comparative example 2, the SEM image of the finished ferric phosphate, and the XRD image of ferric phosphate dihydrate.
[0064] from Figure 4 It can be seen that the primary particles of iron phosphate dihydrate in Comparative Example 2 are in the shape of millet grains. Compared with the morphology of iron phosphate dihydrate in Example 6, the primary particle size of this process is obviously smaller, and the particle development is incomplete. After calcination under the same conditions, the finished iron phosphate grains melt into larger particles with low porosity; the XRD spectrum shows that the phase is still monoclinic, but the overall peak intensity is low.
[0065] Experiment 5 The Fe content, P content, H2O content, iron-phosphorus ratio (Fe / P), specific surface area (BET), and density (TD) of the finished iron phosphates prepared in Example 3, Example 6, Comparative Example 1, and Comparative Example 2 were measured respectively, as shown in Table 1.
[0066] Table 1 Physical and chemical indicators of iron phosphate
[0067] It can be seen from Table 1 that the Fe / P ratio of the finished ferric phosphate prepared by the present invention is above 98%, while that of Comparative Examples 1 and 2 is only 96.43% and 95.29%, respectively, indicating that the finished ferric phosphate prepared by the present invention has complete grain development and high crystallinity.
[0068] After calcination at the same temperature, the specific surface area of the finished iron phosphate prepared by the present invention is maintained at 13.3 m2 / g and 15.2 m2 / g, while that of the comparative example is only 3.6 m2 / g and 3.0 m2 / g. The specific surface area of the present invention is significantly improved compared with the comparative example, indicating that the iron phosphate grains prepared by the present invention are extremely resistant to high temperatures, and most of the iron and phosphorus components are involved in the construction of iron phosphate crystals, so the structure is stable; while the iron phosphate grains prepared in the comparative example are not resistant to burning, part of the iron and phosphorus constitute amorphous iron phosphate, the crystallinity is general, and the crystallization process is insufficient.
[0069] Experiment 6 As a precursor of lithium iron phosphate, the physical and chemical indicators of iron phosphate will directly affect the performance of the back-end finished product. Among them, good crystallinity and high iron-phosphorus ratio are beneficial to the complete crystal structure of iron phosphate, thereby improving the charge and discharge cycle life and rate capacity of lithium iron phosphate. The present invention introduces ferrous sulfate as a catalyst in the conversion process of the iron phosphate precursor, which promotes the phase change of iron phosphate crystals and grain development. Several small experiments are carried out to explore the catalytic mechanism: ① The controlled variable method was used to explore the catalytic nature of ferrous sulfate salts: the synthesis conditions were controlled to be consistent, and two sets of variable experiments were carried out based on the same washed filter cake. Equal amounts of ferrous sulfate (blank group) and sodium sulfate (experimental group) were added during the conversion process. The results showed that the iron-to-phosphorus ratio of the material using ferrous sulfate was 98.7%, much higher than the 96.3% using sodium sulfate. The sulfate concentration and pH value in the mother liquors of the two groups of experiments were similar, with only differences in ferrous ions and sodium ions. The comparison of the results showed that only ferrous ions in ferrous sulfate played a catalytic role in the conversion process.
[0070] ② The process analysis method was used to explore the essential reason for the increase in the iron-to-phosphorus ratio of the finished product after using ferrous sulfate in the conversion process, and the iron content of the mother liquor before and after the conversion was monitored: four sets of conversion process variable experiments were carried out based on the same first-wash filter cake, and the variables were different amounts of ferrous sulfate added. The iron content of the mother liquor before and after the conversion was measured. Before the conversion was heated, the values were 5, 479, 600, and 631 ppm, respectively, and after the discharge, the values were 6, 480, 596, and 624 ppm, respectively. The similar iron content means that ferrous ions did not enter the crystal lattice of the finished product. It can be concluded that ferrous ions mainly act as catalysts in the conversion process, that is, ferrous ions are not consumed before and after the reaction, and the increase in the iron-to-phosphorus ratio of the finished product is not due to the entry of ferrous ions into the ferrous phosphate lattice (since ferrous ions are in a +2 valence state, they will combine with fewer phosphates relative to the +3 valence iron ions in the ferric phosphate crystals when the charge is balanced. If ferrous ions enter the lattice, the phosphorus content of the finished product will decrease, resulting in an increase in the iron-to-phosphorus ratio).
[0071] ③Based on the same washed filter cake, a conversion variable experiment was carried out. No ferrous sulfate was added before the conversion temperature rise (blank group) and ferrous sulfate was added before the conversion temperature rise (experimental group). Other conversion factors were controlled to be the same. By comparison, it was found that the time taken for the slurry to turn white after the start of heating in the experimental group was about 110 minutes, while that in the blank group was 118 minutes. The whitening means that the ammonium iron phosphate phase is completely consumed and changes to the next stage. It can be concluded that ferrous ions participate in and promote the transformation of the ammonium iron phosphate phase. The larger grain size may be due to the fact that both ferrous and ferric iron can bind to phosphate in the mother liquor, and the two compete for nucleation. The introduction of ferrous ions can reduce the number of dihydrate iron phosphate nuclei, thereby increasing the grain size.
[0072] ④ Based on the same washed filter cake, a conversion variable experiment was carried out. Both groups of experiments added equal amounts of phosphoric acid, ferrous sulfate and pure water before the conversion temperature was raised, and the same heating program was set. After the material turned white, excess hydrogen peroxide was added to one of the groups to oxidize the ferrous ions into trivalent ferrous ions (experimental group), and the other group remained unchanged (blank group). Finally, the iron-phosphorus ratio of the finished product of the experimental group was only 96.2%, and the grain size was significantly reduced, while the iron-phosphorus ratio of the blank group reached 98.3%. It can be concluded that ferrous ions also play a catalytic role in the development process of dihydrate iron phosphate grains after whitening. It is speculated that ferrous hydrogen phosphate reduces the phosphorus concentration of the mother liquor, reduces the supersaturation of iron and phosphorus ions in the mother liquor, slows down the crystal growth rate, and makes the crystal development more complete.
[0073] In general: only ferrous ions in ferrous sulfate salts have a catalytic effect, and they have a catalytic effect on the transformation of ammonium ferric phosphate into dihydrate ferric phosphate phase and the development of dihydrate ferric phosphate grains. The larger ferric phosphate grains after catalysis may be due to the competition between ferrous and ferric iron for nucleation with phosphate.
Claims
1. A method for increasing the iron-phosphorus ratio of ferric phosphate material, characterized in that: The steps include: S1. Raw material preparation: prepare 0.5-2.0 mol / L ammonium phosphate solution, 0.5-2.0 mol / L phosphoric acid solution, 0.5-2.0 mol / L titanium dioxide ferrous solution, and 30% hydrogen peroxide; S2, synthesis: the ammonium phosphate solution, titanium dioxide ferrous solution and hydrogen peroxide prepared in step S1 are added into a reaction container, and the mixture is kept warm for 30-60 min to obtain a slurry, and the slurry is filtered and washed until the conductivity of the washing water is less than 4000 μS / cm to obtain a yellow washed filter cake; S3, conversion: weigh 5-15 kg of pure water, add 200-400 g of ferrous sulfate and 200-600 g of the phosphoric acid solution prepared in step S1 to dissolve them, add 2.5-3.5 kg of the yellow first-wash filter cake obtained in step S2, after 15-25 min of slurrying, heat to 90-94 ° C, keep warm for 1 hour, filter and wash with suction to obtain a pink second-wash filter cake; S4, calcination: drying the pink second-wash filter cake to obtain ferric phosphate dihydrate, calcining and crushing the ferric phosphate dihydrate to obtain finished ferric phosphate.
2. A method for increasing the iron-phosphorus ratio of an iron phosphate material as claimed in claim 1, characterized in that: In step S1, the pH of the ammonium phosphate solution is 6.5-7.
5.
3. A method for increasing the iron-phosphorus ratio of an iron phosphate material as claimed in claim 1, characterized in that: In the step S1, the ratio of the amount of substances is ferrous titanium dioxide solution: ammonium phosphate solution = 0.8-1.
2.
4. A method for increasing the iron-phosphorus ratio of an iron phosphate material as claimed in claim 1, characterized in that: In the step S2, the ratio of the amounts of substances is: titanium dioxide ferrous solution: ammonium phosphate solution: hydrogen peroxide = 1: 1.00-1.08: 0.60-0.
65.
5. A method for increasing the iron-phosphorus ratio of ferric phosphate material as claimed in claim 4, characterized in that: In step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: pure water is used as the base, the ammonium phosphate solution and the titanium dioxide ferrous solution are added into the reaction container in parallel, and then the hydrogen peroxide is added.
6. A method for increasing the iron-phosphorus ratio of ferric phosphate material as claimed in claim 5, characterized in that: In the step S2, the feeding rate of the titanium dioxide ferrous solution and the phosphorus source is 100-300 ml / min.
7. A method for increasing the iron-phosphorus ratio of an iron phosphate material as claimed in claim 6, characterized in that: In step S2, the feeding rate of hydrogen peroxide is 5-15 ml / min, and the reaction temperature is 30-60°C.
8. A method for increasing the iron-phosphorus ratio of an iron phosphate material as claimed in claim 4, characterized in that: In step S2, the specific method of adding the ammonium phosphate solution, the titanium dioxide ferrous solution and the hydrogen peroxide solution into the reaction container is: using the titanium dioxide ferrous solution as the base, mixing the ammonium phosphate solution and the hydrogen peroxide solution and then adding them into the reaction container in a single stream.
9. A method for increasing the iron-phosphorus ratio of an iron phosphate material as claimed in claim 8, characterized in that: In the step S2, the ammonium phosphate solution and the hydrogen peroxide are mixed and added in a single stream at a feeding rate of 100-300 ml / min, and the reaction temperature is 30-60°C.
Citation Information
Cited By
Anhydrous iron phosphate as well as preparation method and application thereof
CN120736490A